MOTIVATION AS A FACTOR OF DEVELOPMENT CLOSE TO RELATED SPEECH (Pedagogy of Higher and Secondary Education, 2022)
The article is focuses on the specific of the motive in the development of written speech of pupils at lessons on Ukrainian language learning gas a second one.